Raw Networking. - Neville-Neil, George V. (Communications of the ACM, 2015)
The article presents questions and answers related to computer science. Topics include the costs or benefits of creating a new wireless Internet transport protocol for a business network rather than relying on existing Internet protocols such as transmission control protocol (TCP) or user datagram protocol (UDP); and a discussion of how to test software.